Transcriptional Activity of Heparan Sulfate Biosynthetic Machinery is Specifically Impaired in Benign Prostate Hyperplasia and Prostate Cancer - Suhovskih, Anastasia V.; Tsidulko, Alexandra Y.; Kutsenko, Olesya S.; Kovner, Anna V.; Aidagulova, Svetlana V.; Ernberg, Ingemar; Grigorieva, Elvira V. (Frontiers in Oncology, 2014)
Heparan sulfates (HS) are key components of mammalian cells surface and extracellular matrix. Structure and composition of HS, generated by HS biosynthetic system through non-template driven process, are significantly altered in cancer tissues. The aim of this study was to investigate an involvement of HS metabolic machinery in prostate carcinogenesis. Transcriptional patterns of HS-metabolic enzymes (EXT1, EXT2, NDST1, NDST2, GLCE, 3OST1/HS3ST1, SULF1, SULF2, HPSE) were determined in normal, benign and cancer human prostate tissues and cell lines (PNT2, LNCaP, PC3, DU145). Stability of the HS-metabolic system patterns under the pressure of external or internal stimuli was studied. Overall impairment of transcriptional activity of HS metabolic machinery was detected in benign prostate hyperplasia, while both significant decrease in the transcriptional activity and changes in the expression patterns of HS metabolism-involved genes were shown in prostate tumours. Prostate cancer cell lines possessed specific transcriptional patterns of HS metabolism-involved genes; however expression activity of the system was similar to that of normal prostate PNT2 cells. HS metabolic system was able to dynamically react to different external or internal stimuli in cell type-dependent manner. LNCaP cells were sensitive to the external stimuli (5-aza-deoxycytidin or Trichostatin A treatments; co-cultivation with human fibroblasts), whereas PC3 cells almost did not respond to the treatments. Ectopic GLCE over-expression resulted in transcriptional activation of HS biosynthetic machinery in both cell lines, suggesting an existence of a self-regulating mechanism for the coordinated transcription of HS metabolism-involved genes. Taken together, these findings demonstrate impairment of HS metabolic system in prostate tumours in vivo but not in prostate cancer cells in vitro, and suggest that as a potential microenvironmental biomarker for prostate cancer diagnostics and treatment.